Central nervous system relapse in triple-negative breast cancer patients achieving pathological complete response after neoadjuvant chemotherapy: A retrospective cohort analysis - Gabriel Berlingieri Polho; Yumi Ricucci Shinkado; Leticia Kimie Murazawa; Vinicius Vitor Oliveira; Victor Rocha Pinheiro; Diana del Cisne Pineda Labanda; Romualdo Barroso-Sousa; Luciana Rodrigues Carvalho Barros; Laura Testa; Renata Colombo Bonadio (Breast)
Triple-negative breast cancer (TNBC) is associated with an increased risk of distant metastases. While pathological complete response (pCR) after neoadjuvant chemotherapy predicts favorable outcomes, data suggest it may not uniformly protect against central nervous system (CNS) relapse.This study analyzed 774 TNBC patients to assess recurrence patterns. While CNS recurrences were numerically lower in pCR patients (5.0 % vs 8.8 %, p = 0.11), they represented a significantly higher proportion of all relapses in this group (50.0 % vs 20.2 %, p = 0.003). These results suggest that while pCR reduces overall recurrence risk, there is a distinct pattern of CNS-predominant failure.